Enhancing Meat Quality and Nutritional Value in Monogastric Livestock Using Sustainable Novel Feed Ingredients - José A. M. Prates (Foods)
This study explores the potential of novel feed ingredients for monogastric animals, such as pigs and poultry, to enhance meat quality and nutritional value while reducing the environmental footprint of production. Innovative feed options like black soldier fly larvae, Schizochytrium microalga, Laminaria seaweed, fermented soybean hulls, fortified flaxseed and grape pomace have significantly improved meat quality and nutritional traits. Results indicate that these ingredients enrich meat with omega-3 fatty acids, antioxidants, vitamins and minerals, enhancing nutritional value while improving sensory traits such as flavour, tenderness and colour. For instance, including Laminaria seaweed increased iodine content by up to 45%, while Schizochytrium microalga improved omega-3 deposition by over 70%. The inclusion of grape pomace enhanced oxidative stability and extended meat shelf life. This review also discusses the influence of ingredient composition, inclusion levels and processing techniques, alongside challenges such as regulatory constraints, ingredient cost and palatability. The alignment of these alternative feeds with circular economy principles and sustainability goals further emphasizes their role in reducing environmental impact. By summarising recent advancements, this paper underscores the transformative potential of novel feed ingredients in advancing monogastric meat production towards greater nutritional quality, sustainability and consumer acceptance.